The development and assessment of a predicting nomogram for the recovery of immediate urinary continence following laparoscopic radical prostatectomy - Gu, Zhuoran; Zheng, Zongtai; Zhang, Wentao; Mao, Shiyu; Wang, Shuai; Geng, Jiang; Yao, Xudong (Frontiers in Surgery, 2023)
Purpose: This study aimed to develop a nomogram to predict the recovery of immediate urinary continence in laparoscopic radical prostatectomy (LRP) patients. Methods: A prediction model was developed based on a dataset of 154 LRP patients. Immediate urinary continence was defined as free from using pads within 7 days after the removal of the urinary catheter. The least absolute shrinkage and selection operator regression (LASSO) model was applied to screen the features. Multivariate logistic regression analysis was used to establish prediction model integrating the features selected from the LASSO regression analysis. Receiver operating curve (ROC), calibration and decision curve analysis (DCA) were used to assess the model’s discrimination, calibration and clinical utility. Results: The identified features of the prediction model included age, body mass index (BMI) and three pelvic anatomic parameters measured by MRI: membranous urethral length (MUL), intravesical prostatic protrusion length (IPPL) and puborectalis muscle width (PMW). The nomogram showed good discrimination with an are under the curve(AUC) of 0.914 (95% CI: 0.865-0.959, p<0.001). Moreover, good calibration was showed in the model. Lastly, DCA showed that the nomogram was clinically useful. Conclusion: The developed novel nomogram that can predict the possibility for post-prostatectomy patients to recover immediate urinary continence could be used as a counseling tool to explain urinary incontinence to patients after LRP.